Social Policy Transformation and Business Environment Improvement: a Comparative Analysis Based on China and Russia - Deyou Xu (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
Over the past four decades, the economy and society of China and Russia have undergone transformation. Relevant social policies and business environments have constantly changed. So have the ways of interaction among governments, enterprises and citizens. In the relationship between government and citizen, China and Russia have walked different paths in choosing and adjusting social policies, but both have steadily improved people’s well-being. In the relationship between government and business, both countries have achieved significant improvements in business environment through supply-side reforms of public goods and institutions. The theoretical relationship between government and citizen and that between government and business are embodied in social policy and business environment in reality. However, the two are not parallel, but interact with each other and are nested in each other. The government plays a leading role, and its interaction with enterprise and citizen tests the governance systems and capabilities of Beijing and Moscow.